Tracheal stenosis in a Holstein cow - Molossi,Franciéli Adriane (2020)
ABSTRACT: Tracheal stenosis, also known as “Honker syndrome”, is characterized by tracheal edema and hemorrhage, leading to partial obstruction of the lumen; therefore, death. Its etiology is not yet well elucidated. A 3-year-old Holstein cow, with a history of dyspnea, and a large amount of reddish foam flowing from the mouth and nose, had died after 10 minutes of clinical signs. Macroscopic examination revealed focally extensive hemorrhage and clot organization in tracheal mucosa extending to the submucosa, surrounded by well-differentiated fibrous connective tissue. In adjacent mucosa was observed moderate multifocal inflammatory infiltrate composed by lymphocytes and plasma cells, as well as moderate squamous cell metaplasia. The bacterial culture showed growth of contaminant and environmental bacteria and the RT-PCR to detect Herpesvirus 1 (BoHV-1) and 5 (BoHV-5) was negative. To the author’s knowledge, this is the first report of tracheal stenosis in South America, as well as the first report of this condition described in a Holstein cow.